Metabolic obesity phenotypes and risk of ischemic stroke: The Rural Chinese Cohort Study - Cao, Lu; Zhu, Lin; Zhang, Wei; Zhang, Ming; Hu, Dongsheng; Wang, Que (Frontiers in Nutrition, 2026)
BackgroundThe association of metabolic obesity phenotypes and ischemic stroke remains controversial. We aimed to determine the risk of ischemic stroke according to metabolically healthy and obesity status.MethodsA total of 14,707 study participants from The Rural Chinese Cohort Study (RCCS) who were free of stroke and cardiovascular disease (CVD) were stratified by metabolic risk and body mass index (BMI) status at baseline during 2007–2008 and further followed up during 2013–2014. Hazard ratio (HR) and 95% confidence intervals (CIs) of incident ischemic stroke associated with different metabolic-obesity categories were estimated by using Cox regression analysis.ResultsDuring a median follow-up of 6.02 years, we identified 522 newly diagnosed ischemic stroke cases. Risk of ischemic stroke was increased with MHO (HR: 1.87; 95%CI: 0.25–14.18), metabolically unhealthy normal weight (MUNW; HR: 2.36, 95%CI: 1.40–3.98), and metabolically unhealthy obesity (MUO; HR: 3.22, 95%CI: 1.84–5.62) phenotypes as compared with metabolically healthy normal weight (MHNW). In all, 41.3% of people with general obesity had 1 or 2 metabolic risk factors. Both groups had greater risk of ischemic stroke than MHNW people. Sensitivity analyses (considering abdominal obesity instead of general obesity) gave similar findings as the main analyses.ConclusionBoth MUO and MUNW phenotypes are risk factors of ischemic stroke. Early identification and targeted management of MUNW phenotype may have potential clinical implication for future stroke prevention and control.